Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Ulang Produk Customcase Handphone dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Tntshop3 Semarang) - Saputri, Dian Mutiara; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2016)
This study aim to analyze the effect of variants product, perceptions of price and service   quality   to   repurchase  intention   in   Tntshop3   products  through   customer satisfactions as intervening variable on product users Tntshop3. Variants products, perceptions of price and service quality are the reasons of consumer when selecting and alsho repurchasing  customcase  mobile  phone  products  which  is  one  of important consumer needs.In this case use three independent variables with one intervening variables and the dependent variable.  The population are customers Tntshop3. This research uase as a sample of 100 respondents by the criteria have been using the services of Hest'in Modiste more than twice. Then the data were analyzed using multiple regression analysis channeled through the SPSS program. Based on the research results, the result that variants product, perceptions of price and service quality positive effect on customer satisfaction with the regression coefficient is Y1 = 0,212X1+0,218X2+0,498X3    and customer satisfaction has positive effect on the repurchase intention with the regression coefficient is Y2 = 0,693Y1+e.